Zu den Effekten von Gesundheitsreform- und Gesundheitsstrukturgesetz auf den Arzneimittelmarkt: auf dem Weg von der korporativen zur staatlichen Regulierung? - Manfred Erbsland; Eberhard Wille (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
From the viewpoint of regulation, this paper investigates the effects of both the Health Care Refonn Act (Gesundheitsreformgesetz, GRG) and the Structural Health Care Act (Gesundheitsstrukturgesetz, GSG) on phannaceutical markets. Apart from the change in the intensity of regulation, the main focus is on the relative significance of self-regulation (or corporatism) on the one hand, and govemment regulation on the other. As our analysis demonstrates, in contrast to GRG, the impact of GSG has been - at least temporarily - to shift emphasis away from corporatism towards regulation directly imposed by govemment.
Keywords: 330